The Inflammasome Contributes to Depletion of the Ovarian Reserve During Aging in Mice - Lliberos, Carolina; Liew, Seng H.; Mansell, Ashley; Hutt, Karla J. (Frontiers in Cell and Developmental Biology, 2021)
Ovarian ageing is a natural process characterised by follicular depletion and a reduction in oocyte quality, resulting in loss of ovarian function, cycle irregularity and eventually infertility and menopause. The factors that contribute to ovarian ageing have not been fully characterised. Activation of the NLRP3 inflammasome has been implicated in age-associated inflammation and diminished function in several organs. In this study, we used Asc-/- and Nlrp3-/- mice to investigate the possibility that chronic low-grade systemic inflammation mediated by the inflammasome contributes to diminished ovarian reserves as females age. Pro-inflammatory cytokines, IL-6, IL-18 and TNF-α, were decreased in the serum of ageing Asc-/- mice compared to WT. Within the ovary of reproductively aged Asc-/- mice, mRNA levels of major pro-inflammatory genes Tnfa, Il1a and Il1b were decreased, and macrophage infiltration was reduced compared to age-matched WT controls. Notably, suppression of the inflammatory phenotype in Asc-/- mice was associated with retention of follicular reserves during reproductive ageing. Similarly, the expression of intraovarian pro-inflammatory cytokines was reduced, and follicle numbers were significantly elevated, in ageing Nlrp3-/- mice compared to WT controls. These data suggest that inflammasome-dependent inflammation contributes to the age-associated depletion of follicles and raises the possibility that ovarian ageing could be delayed, and fertile window prolonged, by suppressing inflammatory processes in the ovary.